Respuesta :
Hello,
To solve for f(6) and g(20), simply replace x for 6 in the f(x) equation and replace x for 20 in the g(x) equation.
So, we have:
f(6) = (6)(2) + 1 = 12 + 1 = 13
g(20) = 3(20) + 1 = 61
So, if f(6) = 13 and g(20) = 61, then f(6) + g(20) = 13 + 61 = 74
Hope this helps!
To solve for f(6) and g(20), simply replace x for 6 in the f(x) equation and replace x for 20 in the g(x) equation.
So, we have:
f(6) = (6)(2) + 1 = 12 + 1 = 13
g(20) = 3(20) + 1 = 61
So, if f(6) = 13 and g(20) = 61, then f(6) + g(20) = 13 + 61 = 74
Hope this helps!